2021
DOI: 10.1111/ocr.12506
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional soft tissue changes in orthodontic extraction and non‐extraction patients: A prospective study

Abstract: Aesthetic components play a considerable role in the considerations of the orthodontist. The majority of orthodontic treatment plans carried out today carefully considers the face physiognomy and cautiously endeavours to preserve or improve a pleasing appearance. 1 Extractions are still a treatment choice in orthodontics to establish good dental aesthetics and function in patients. 2 Several were the motivation to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…This agrees with the changes in the upper and lower lips described in two previous 3D studies. These found significant correlations between incisor position and vermilion angles, vermilion height, and surface area in the extraction groups 23,24 . Furthermore, we detected hollowing of the cheeks and temples in some patients in the maximum anchorage group.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This agrees with the changes in the upper and lower lips described in two previous 3D studies. These found significant correlations between incisor position and vermilion angles, vermilion height, and surface area in the extraction groups 23,24 . Furthermore, we detected hollowing of the cheeks and temples in some patients in the maximum anchorage group.…”
Section: Discussionmentioning
confidence: 55%
“…These found significant correlations between incisor position and vermilion angles, vermilion height, and surface area in the extraction groups. 23,24 Furthermore, we detected hollowing of the cheeks and temples in some patients in the maximum anchorage group. These changes were similar to the "bracket face" phenomenon, which is the soft tissue depression in the cheeks and temples during orthodontic treatment noticed by Chinese female patients.…”
Section: Discussionmentioning
confidence: 83%
“…Adding 3D facial information to an intraoral scan benefits a more detailed analysis in cases of asymmetry and cleft lip and/or palate patients [76,77]. Research has underlined that soft tissue information derived from facial scans favors the reliability of the evaluation of the outcome in orthognathic and extraction cases [78,79].…”
Section: Alignersmentioning
confidence: 99%
“…Rongo et al shows that a 3D stereophotogrammetric analysis allows for a more comprehensive assessment of the facial soft tissue effects by extraction and non-extraction treatment. 31 Etemad et al applied AI in this extraction issue and demonstrated that a denoise machine learning technique could improve the prediction for a diverse patient population. 32 We sincerely appreciate the opportunity to serve as the guest editors for this issue and wish to thank the editor-in-chief, Dr Ambra Michelotti and Wiley.…”
Section: G U E S T E D I T O R I a L Artificial Intelligence And Mach...mentioning
confidence: 99%
“…This decision is not made simply based on morphological dental and/or skeletal problems, rather it is influenced by various factors. Rongo et al shows that a 3D stereophotogrammetric analysis allows for a more comprehensive assessment of the facial soft tissue effects by extraction and non‐extraction treatment 31 . Etemad et al applied AI in this extraction issue and demonstrated that a denoise machine learning technique could improve the prediction for a diverse patient population.…”
mentioning
confidence: 99%